PERANAN KEPALA DESA DALAM MENINGKATKAN KEPUASAN KERJA APARAT DESA MOKUPO KECAMATAN KARAMAT KABUPATEN BUOL - Sondeng, Ahmad (STISIPOL Mujahidin Buol, 2023)
This research aims to determine and analyze the role of the village head in increasing job satisfaction for Mokupo Village officials, Karamat District, Buol Regency. The research method used is a quantitative research method using descriptive analysis, using population and samples, and research procedures using observation, interviews, and questionnaires. The research results show that the role of leaders in the workplace is very important because it can motivate employees to work well, act as leaders in decision-making, and play an important role in the Mokupo community. Leaders must actively participate, influence, and develop the workplace, ensuring a positive work environment. A leader's role also includes fostering respect and honor, good working conditions, and fostering social interactions. The relationship between leaders and employees is critical to achieving better performance and fostering a positive work environment.